Chemerin Elicits Potent Constrictor Actions via Chemokine‐Like Receptor 1 (CMKLR1), not G‐Protein‐Coupled Receptor 1 (GPR1), in Human and Rat Vasculature. Issue 10 (October 2016) - Kennedy, Amanda J.; Yang, Peiran; Read, Cai; Kuc, Rhoda E.; Yang, Lucy; Taylor, Emily J. A.; Taylor, Colin W.; Maguire, Janet J.; Davenport, Anthony P.
Abstract : Background: Circulating levels of chemerin are significantly higher in hypertensive patients and positively correlate with blood pressure. Chemerin activates chemokine‐like receptor 1 (CMKLR1 or ChemR23) and is proposed to activate the "orphan" G‐protein‐coupled receptor 1 (GPR1), which has been linked with hypertension. Our aim was to localize chemerin, CMKLR1, and GPR1 in the human vasculature and determine whether 1 or both of these receptors mediate vasoconstriction. Methods and Results: Using immunohistochemistry and molecular biology in conduit arteries and veins and resistance vessels, we localized chemerin to endothelium, smooth muscle, and adventitia and found that CMKLR1 and GPR1 were widely expressed in smooth muscle. C9 (chemerin149–157) contracted human saphenous vein (pD2 =7.30±0.31) and resistance arteries (pD2 =7.05±0.54) and increased blood pressure in rats by 9.1±1.0 mm Hg at 200 nmol. Crucially, these in vitro and in vivo vascular actions were blocked by CCX832, which we confirmed to be highly selective for CMKLR1 over GPR1. C9 inhibited cAMP accumulation in human aortic smooth muscle cells and preconstricted rat aorta, consistent with the observed vasoconstrictor action. Downstream signaling was explored further and, compared to chemerin, C9 showed a bias factor=≈5000 for the Gi protein pathway, suggesting that CMKLR1 exhibits biased agonism. Conclusions: Our data suggest that chemerin acts at CMKLR1, but not GPR1, to increase blood pressure. Chemerin has an established detrimental role in metabolic syndrome, and these direct vascular actions may contribute to hypertension, an additional risk factor for cardiovascular disease. This study provides proof of principle for the therapeutic potential of selective CMKLR1 antagonists.